Bivelocity Hydrodynamics of Micro-Channel Couette Flow. - Walls, Peter. (2017)
Abstract: A nonkinetic approach is adopted in this thesis to numerically predict the profiles of a Maxwellian ideal gas in a micro-channel geometry. Our analysis utilizes a full set of mechanically and thermodynamically consistent volume-diffusion hydrodynamic equations. Bivelocity theory predicts, contrary to current investigations, a no-slip velocity at the wall in planar Couette flow for rarefied gas flows. This thesis was motivated by the recent success of Bivelocity hydrodynamics in explaining traditionally non-continuum phenomenon in a physically sound manner. The results are compared and contrasted with the Burnett equations, which show that the predictions are fundamentally different from those previously obtained in similar analyses. It is concluded that more experimental data will be needed to make a determination as to which model should be used. Suggestions for experimental verification, motivated by our numerical results, are also presented.; Thesis (M.S.)--Tufts University, 2013.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Behrouz Abedian.; Committee: Mark Kachanov, and Christoph Börgers.; Keyword: Mechanical engineering.